Cerium-doped calcium phosphates precipitated on bacterial cellulose platform by mineralization - Sousa, Ricardo Barbosa; Dametto, Alessandra Cristina; Sabio, Rafael Miguel [UNESP]; Carvalho, Renata Aquino de; Vieira, Ewerton Gomes; Amaral Oliveira, Andre Felipe do; Ribeiro, Lara Kelly; Barud, Hernane S.; Silva-Filho, Edson C. (Elsevier B.V., 2020)
Bacterial cellulose (BC) membranes biosynthesized by Komagataeibacter rhaeticus AF1 strain were used as a platform for precipitating cerium-doped calcium phosphates (Ce:CaP), which were synthetized by successive soaking of BC membranes in solutions containing Ca2+, PO43- and Ce3+ precursor ions. After obtaining the as-prepared composites, BC-Ce:CaP was submitted to a thermal treatment at 600 degrees C for 3 h, and Ce:CaP was characterized by scanning electronic microscopy (SEM), energy dispersive X-ray spectrometry (EDX), thermogravimetric analysis (TG), derivative thermogravimetric analysis (DTG) and X-ray diffraction (XRD). Ce:CaP presented hydroxyapatite, chlorapatite and buchwaldite (sodium calcium phosphate) phases and revealed a trabecular structure composed per nanowires with interconnected pores. Furthermore, BC-Ce:CaP and Ce:CaP show cell viability and has been suggested for use as a mineral scaffold.
Keywords: Polysaccharide; Lanthanide ions; Bioceramics; Nanocomposite